Physical and Organlopetic Properties of Nuggets from Domestic Chicken (Gallus domesticus) Meat with Different Corn Flours as Filler - Wahidah Ma'ruf; Djalal Rosyidi; Lilik Eka Radiati; Purwadi Purwadi (Research Journal of Life Science, 2019)
The research aims to understand the physical and organoleptic properties of the Indonesian domestic chicken (Gallus domesticus) nugget made with different corn flours as filler. The research was done in two research steps. The first step was to observe the physical properties of the chicken nugget through a completely randomized design, where five different corn flours were used and measured for six times each. The second step was to observe the organoleptic properties of the chicken nugget through two-factorials completely randomized design, where five different panellists (P1, P2, P3, P4, and P5) were the first factor and different corn flours were the second factor. The corn flours used in this research were yellow-corn (J1); fluffy-corn (J2); purple-corn (J3); Provit A1-corn (J4); and Provit A2-corn (J5) flour. The measured variables include cooking loss, flavor, aroma, texture, and color of the chicken nugget. The results showed that J1 chicken nugget had the lowest cooking loss at 1.27%, while the organoleptic measurements showed that J4 chicken nugget had the best organoleptic properties. The research concluded that the usage of Provit A1-corn (J4) flour would give the best overall physical and organoleptic properties of chicken nugget made from domestic chicken meat.